2012
DOI: 10.1037/a0030348
|View full text |Cite
|
Sign up to set email alerts
|

How macaques view familiarity and gaze in conspecific faces.

Abstract: The pattern of visual fixations on an image depends not only on the image content but also on the viewer's disposition and on the function (or pathology) of underlying neural circuitry. For example, human viewers display changes in viewing patterns toward face images that differ in gaze direction or in the viewer's familiarity with the face. Macaques share many face processing abilities with humans, and their neural circuitry is used to understand perception across species, yet their viewing responses to gaze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 67 publications
(91 reference statements)
8
29
0
Order By: Relevance
“…These associations indicate that, in the context of juice allocation, mutual gaze could express an intrinsic motivation for social affiliation. Thus, consistently with other observations, we suggest that monkeys' eye contact can also represent a form of positive social interaction (44,(48)(49)(50). The vicarious reward hypothesis suggests that viewing a conspecific receiving juice might activate, through some form of mirror mechanism, the same reward circuit as an actual drop of juice (33).…”
Section: Discussionsupporting
confidence: 62%
“…These associations indicate that, in the context of juice allocation, mutual gaze could express an intrinsic motivation for social affiliation. Thus, consistently with other observations, we suggest that monkeys' eye contact can also represent a form of positive social interaction (44,(48)(49)(50). The vicarious reward hypothesis suggests that viewing a conspecific receiving juice might activate, through some form of mirror mechanism, the same reward circuit as an actual drop of juice (33).…”
Section: Discussionsupporting
confidence: 62%
“…Studies investigating social perception have almost exclusively used images of faces cropped from the body, finding that both rhesus macaques (Keating and Keating, 1982; Mendelson et al, 1982; Wilson and Goldman-Rakic, 1994; Guo et al, 2003, 2006; Gothard et al, 2004, 2009; Deaner et al, 2005; Ghazanfar et al, 2006; Nahm et al, 2008; Leonard et al, 2012) and humans (Haith et al, 1977; Walker-Smith et al, 1977; Janik et al, 1978; Althoff and Cohen, 1999; Henderson et al, 2005) prefer to view faces, particularly the eye region, compared to other stimuli. However, in natural settings, faces are rarely seen in isolation from bodies and other individuals and objects.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, these studies have shown that the spatial distribution of eye fixations is modulated by conspecificity, the eyeregion of conspecific faces receiving more attention than other face parts. Familiarity, defined as being an in-group member, and direct versus averted gaze also influenced single face scanning in macaques (Leonard et al 2012). Again, the eyes of familiar individuals received more attention than the eyes of unfamiliar conspecifics.…”
Section: Introductionmentioning
confidence: 99%